ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TINGKAT PENGUNGKAPAN INTERNET CORPORATE REPORTING (Studi Empiris pada Perusahaan Sektor Manufaktur yang Listing di Bursa Efek Indonesia (BEI) pada Tahun 2013) - Aditya Rahadhian; Aditya Septiani (Diponegoro Journal of Accounting, 2014)
This study aims to examine influence of corporate governance mechanism to the level of internet corporate reporting disclosure on manufacturer company who listed in Indonesia Stock Exchange in 2013. The dependent variable in this study is the level of internet corporate reporting disclosure measured by total score of 49 items on internet disclosure index, while the independent variable is managerial ownership, public ownership, the number of independent commissioner, audit committee’s meeting frequency, audit committee’s competency and also company size, profitability, liquidity, leverage as control variable. The data used in this study is a secondary data that collected by using purposive sampling method. Sample of 47 companies from 136 populations from manufacturer companies who listed in Indonesia Stock Exchange in 2013. This study used multiple regression for data analysis. The results of this study showed that the variable number of independent commissioner positively influence the level of internet corporate reporting disclosure. Other variables such as managerial ownership, public ownership, audit committee’s meeting frequency, and audit committee’s competency influence the level of internet corporate reporting disclosure is not proven. In this research model, shows the independent variable managerial ownership, public ownership, the number of independent commissioner, audit committee’s meeting frequency, audit committee’s competency and also company size, profitability, liquidity, leverage as control variable can only explain the variation in the level of internet corporate reporting disclosure of 26%